2007
DOI: 10.1016/j.chembiol.2007.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Knockout of Pantothenate Kinase Reveals the Metabolic and Genetic Program Responsible for Hepatic Coenzyme A Homeostasis

Abstract: Coenzyme A (CoA) is the major acyl group carrier in intermediary metabolism. Hopantenate (HoPan), a competitive inhibitor of the pantothenate kinases, was used to chemically antagonize CoA biosynthesis. HoPan dramatically reduced liver CoA and mice developed severe hypoglycemia. Insulin was reduced, glucagon and corticosterone were elevated, and fasting accelerated hypoglycemia. Metabolic profiling revealed a large increase in acylcarnitines, illustrating the role of carnitine in buffering acyl groups to maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
137
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 109 publications
(147 citation statements)
references
References 57 publications
5
137
1
Order By: Relevance
“…Although a-pantothenic acid has not previously been studied in the context of PanK and/or CoA inhibitors, HoPan was shown to act as a competitive inhibitor of a murine PanK II (MmPanK1a) and to negatively affect CoA levels in mice in vivo [24]. The same result was found in insect cells [25].…”
Section: Pantothenamide Library and Study Designsupporting
confidence: 70%
See 1 more Smart Citation
“…Although a-pantothenic acid has not previously been studied in the context of PanK and/or CoA inhibitors, HoPan was shown to act as a competitive inhibitor of a murine PanK II (MmPanK1a) and to negatively affect CoA levels in mice in vivo [24]. The same result was found in insect cells [25].…”
Section: Pantothenamide Library and Study Designsupporting
confidence: 70%
“…The same result was found in insect cells [25]. By contrast, E. coli type I PanK (EcPanK I ), which is known to accept a range of pantothenic acid analogues [21], does not accept HoPan as a substrate, nor is it significantly inhibited by it [15,24,26]. This diverse response indicated that such modifications in the Pan structure could successfully be used to probe PanK activity and inhibition.…”
Section: Pantothenamide Library and Study Designmentioning
confidence: 57%
“…The lower contribution of PanK2 to the total PanK activity in mouse brain compared to humans and its localization in the cytosol rather than the mitochondria are two factors that need to be considered in the understanding of the role of PanK isoforms in CoA homeostasis and in the development of a mouse model that recapitulates the molecular aspects of human PKAN disease. A recent report [23] suggests that pantothenate-deficiency in wild-type mice leads to a movement disorder that may provide a phenocopy for human PKAN disease, whereas pantothenate-deficiency in Pank2 knockout mice causes precipitous death, similar to the global mouse knockout of all pantothenate kinase isoforms with a chemical inhibitor [22]. The same analysis was conducted on mRNA from specific regions of the murine (C) and human (D) brain.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Pank1 Ϫ/Ϫ Pank2 Ϫ/Ϫ double knock-out mice are unable to metabolize fats and ketones resulting in early postnatal death (16), and Pank1 Ϫ/Ϫ Pank3 Ϫ/Ϫ and Pank2 Ϫ/Ϫ Pank3 Ϫ/Ϫ double knock-out mice are both embryonic lethal. A chemical knockout of all pantothenate kinases in adult mice resulted in an 80% reduction in hepatic CoA levels and death within days (17). It is clear from these various studies that CoA homeostasis is critical to support mammalian oxidative metabolism and neuronal function.…”
mentioning
confidence: 99%